Ophthalmic symptoms before and after surgery for tuberculum sellae meningioma - K.S. Iegorova; V.V. Musulevska (Ukrainian Society of Ophthalmologists, 2024)
Purpose: To review the features of ophthalmic symptoms before and after surgery for tuberculum sellae meningioma (TSM). Material and Methods: We reviewed the results of diagnostic assessment and outcomes of 91 patients ((182 eyes; 70 (76.9%) women and 21 (23.1%) men; mean age, 48.4% ± 1.7 years) treated for TSM with or without diaphragm sellae involvement at the Romodanov institute during 2014 through 2023. Patients underwent clinical neurological and eye examination and neuroimaging procedures. The results were reviewed for analysis and generalization of visual functions to calculate visual abnormality scores as per the guidelines of the German Ophthalmological Society. Results: Asymmetric visual field defects were observed in 41 (45.1%) patients with a bilateral disease, and unilateral visual field defects, in 23 (25.3%) patients, which was caused by both tumor compression of the anterior chiasm and optic canal invasion. Of the 74 (81.3%) patients with optic atrophy, 45 had unilateral optic atrophy, and 29, bilateral optic atrophy. Postoperatively, visual function improved, worsened and did not change in 72.5%, 7.7%, and 19.8% of patients, respectively. Conclusion: The approach to TSM resection should be tailored to the degree of optic canal invasion, tumor size and tumor relationship with the surrounding neural and vascular structures. On this basis, transcranial resection was performed in 68.1%, and endoscopic endonasal resection of TSM, in 31.9% of patients. The mean visual acuity improved from 0.44 ± 0.07 at preoperative to 0.69 ± 0.04 at postoperative evaluation (p < 0.001), and the average mean defect (MD) improved from 15.34 ± 0.78 dB at preoperative to 9.14 ± 0.64 dB at postoperative evaluation (p < 0.001).